Prognostic Significance of Preoperative Controlling Nutritional Status (CONUT) Score in Patients Undergoing Hepatic Resection for Hepatocellular Carcinoma: A Multi-institutional Study - Harimoto, Norifumi; Yoshizumi, Tomoharu; Inokuchi, Shoichi; Itoh, Shinji; Adachi, Eisuke; Ikeda, Yasuharu; Uchiyama, Hideaki; Utsunomiya, Tohru; Kajiyama, Kiyoshi; Kimura, Koichi; Kishihara, Fumiaki; Sugimachi, Keishi; et al. (Annals of surgical oncology, 2018)
Background The Controlling Nutritional Status (CONUT) score is an objective tool that is widely used to assess the nutritional status in patients, including those with cancer. The relationship between the CONUT score and prognosis in patients who have undergone hepatic resection has not been evaluated in a multi-institutional study. Methods Data were retrospectively collected for 2461 consecutive patients with hepatocellular carcinoma (HCC) who had undergone hepatic resection with curative intent at 13 institutions between January 2004 and December 2015. Patients were assigned to two groups: preoperative CONUT scores ≤ 3 (low CONUT score) and ≥ 4 (high CONUT score). Clinicopathological characteristics, surgical outcomes, and long-term survival were compared using propensity score matching analysis. Results Of the 2461 patients, 540 (21.9%) had high (≥ 4) and 1921 (78.1%) had low (≤ 3) preoperative CONUT scores. Overall, a high CONUT score was significantly associated with older age, female sex, low body mass index, low serum albumin, high serum total bilirubin, low lymphocyte count, low serum cholesterol, shorter prothrombin time, higher indocyanine green retention test at 15 min, Child–Pugh B (vs. A), liver cirrhosis, minor resection, shorter operation time, massive blood loss, blood transfusion, and postoperative complications. After propensity score matching, a higher CONUT score was significantly associated with poor overall survival (OS) and recurrence-free survival (RFS) using multivariate analysis. Conclusions This retrospective, multi-institutional analysis showed that, in patients who undergo curative hepatectomy for HCC, the preoperative CONUT score is predictive of worse OS and RFS, even after propensity score matching analysis.